2013
DOI: 10.1111/tan.12115
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous‐peptide‐dependent alloreactivity: new scientific insights and clinical implications

Abstract: T-cell alloreactivity is generated via immune responsiveness directed against allogeneic (allo) human leucocyte antigen (HLA) molecules. Whilst the alloresponse is of extraordinary potency and frequency, it has often been assumed to be less peptide-specific than conventional T-cell reactivity. Recently, several human studies have shown that both alloreactive CD8(+) and CD4(+) T cells exhibit exquisite allo-HLA and endogenous peptide specificity that has also underpinned tissue-specific allorecognition. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 86 publications
(120 reference statements)
0
16
0
Order By: Relevance
“…Infection- and vaccine-induced memory T cells have a high cross-reactive potential against allo-MHC molecules (43). Substitutions at key residues in the PBS (Table 3) are expected to modify the endogenous peptide repertoire bound to allo-HLA molecules, thereby increasing the cross-reactive potential of virus-specific memory T cells.…”
Section: Recognition Of Hla-c Incompatibilities By Alloreactive T Cellsmentioning
confidence: 99%
“…Infection- and vaccine-induced memory T cells have a high cross-reactive potential against allo-MHC molecules (43). Substitutions at key residues in the PBS (Table 3) are expected to modify the endogenous peptide repertoire bound to allo-HLA molecules, thereby increasing the cross-reactive potential of virus-specific memory T cells.…”
Section: Recognition Of Hla-c Incompatibilities By Alloreactive T Cellsmentioning
confidence: 99%
“…Originally, it was thought that alloreactivity was mediated by TCR recognition of foreign MHC (“MHC-centric”). More recently, however, it has become increasingly apparent that the alloreactive TCR/pMHCI interaction can be highly peptide-dependent (“peptide-centric”) (4648). In fact, it appears that peptide specificity is profound when self-MHCI and foreign-MHCI are closely related (49).…”
Section: Implications Of Mhci-bound Peptide Length Preference For Dismentioning
confidence: 99%
“…The reactivity of T cells with incompatible HLA molecules is unexpected as T cells are educated to recognize viral and bacterial peptides in the context of self HLA. Recent studies have shown that reactivity with incompatible HLA is based on crossreactivity of T cells meant to recognize viral peptides in self HLA [21,22] . As a consequence, a patient, who has never been confronted with foreign HLA but has experienced several infections, can have memory T cells to foreign HLA antigens on a graft affecting transplant outcome.…”
Section: Anti-hla Antibody Responsementioning
confidence: 99%